RNA‐sequence‐based microRNA expression signature in breast cancer: tumor‐suppressive miR‐101‐5p regulates molecular pathogenesis - Hiroko Toda; Naohiko Seki; Sasagu Kurozumi; Yoshiaki Shinden; Yasutaka Yamada; Nijiro Nohata; Shogo Moriya; Tetsuya Idichi; Kosei Maemura; Takaaki Fujii; Jun Horiguchi; Yuko Kijima; et al. (Molecular Oncology, 2020)
Aberrantly expressed microRNA (miRNA) are known to disrupt intracellular RNA networks in cancer cells. Exploring miRNA‐dependent molecular networks is a major challenge in cancer research. In this study, we performed RNA‐sequencing of breast cancer (BrCa) clinical specimens to identify tumor‐suppressive miRNA in BrCa. In total, 64 miRNA were identified as candidate tumor‐suppressive miRNA in BrCa cells. Analysis of our BrCa signature revealed that several miRNA duplexes (guide strand/passenger strand) derived from pre‐miRNA were downregulated in BrCa tissues (e.g. miR‐99a‐5p/‐3p, miR‐101‐5p/‐3p, miR‐126‐5p/‐3p, miR‐143‐5p/‐3p, and miR‐144‐5p/‐3p). Among these miRNA, we focused on miR‐101‐5p, the passenger strand of pre‐miR‐101, and investigated its tumor‐suppressive roles and oncogenic targets in BrCa cells. Low expression of miR‐101‐5p predicted poor prognosis in patients with BrCa (overall survival rate: P = 0.0316). Ectopic expression of miR‐101‐5p attenuated aggressive phenotypes, e.g. proliferation, migration, and invasion, in BrCa cells. Finally, we identified seven putative oncogenic genes (i.e. High Mobility Group Box 3, Epithelial splicing regulatory protein 1, GINS complex subunit 1 (GINS1), Tumor Protein D52, Serine/Arginine‐Rich Splicing Factor Kinase 1, Vang‐like protein 1, and Mago Homolog B) regulated by miR‐101‐5p in BrCa cells. The expression of these target genes was associated with the molecular pathogenesis of BrCa. Furthermore, we explored the oncogenic roles of GINS1, whose function had not been previously elucidated, in BrCa cells. Aberrant expression of GINS1 mRNA and protein was observed in BrCa clinical specimens, and high GINS1 expression significantly predicted poor prognosis in patients with BrCa (overall survival rate: P = 0.0126). Knockdown of GINS1 inhibited the malignant features of BrCa cells. Thus, identification of tumor‐suppressive miRNA and molecular networks controlled by these miRNA in BrCa cells may be an effective strategy for elucidation of the molecular pathogenesis of this disease.